2021
DOI: 10.3389/fonc.2021.706011
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Landscapes of Long Noncoding RNA in Thyroid Carcinoma: Biological Functions and Clinical Significance

Abstract: Thyroid carcinoma (TC) is one of the most prevalent primary endocrine tumors, and its incidence is steadily and gradually increasing worldwide. Accumulating evidence has revealed the critical functions of long noncoding RNAs (lncRNAs) in the tumorigenesis and development of TC. Many TC-associated lncRNAs have been documented to be implicated in TC malignant behaviors, including abnormal cell proliferation, enhanced stem cell properties and aggressiveness, and resistance to therapeutics, through interaction wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 155 publications
(176 reference statements)
0
8
0
Order By: Relevance
“…GSEA analyses showed that enrichment of the PI3K/AKT signaling pathway was significant after FOXP4-AS1 knockdown ( Figure 6C ). The PI3K/AKT pathway appears to be one of the major signaling pathways that contribute to tumorigenesis of thyroid carcinoma ( 6 ). The expression level of p-AKT was impaired significantly in K1 and TPC1 cells following FOXP4-AS1 overexpression by Western blotting, whereas it increased after FOXP4-AS1 knockdown ( Figures 6D, E ) .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…GSEA analyses showed that enrichment of the PI3K/AKT signaling pathway was significant after FOXP4-AS1 knockdown ( Figure 6C ). The PI3K/AKT pathway appears to be one of the major signaling pathways that contribute to tumorigenesis of thyroid carcinoma ( 6 ). The expression level of p-AKT was impaired significantly in K1 and TPC1 cells following FOXP4-AS1 overexpression by Western blotting, whereas it increased after FOXP4-AS1 knockdown ( Figures 6D, E ) .…”
Section: Resultsmentioning
confidence: 99%
“…The PI3K/AKT/mTOR signaling pathway was featured strongly in regulating cellular metabolism, proliferation, survival, and apoptosis ( 29 ). Hyperactivation of the PI3K/AKT/mTOR signaling pathway is proved to contribute to the development of various cancers, including thyroid carcinoma ( 6 , 27 , 39 ). Although the activation of PI3K/AKT/mTOR signaling is observed in almost all PTC patients, the upstream regulator of this signaling is still to be determined.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on their subcellular localization ( Quinn and Chang, 2016 ), lncRNAs can be further divided into nuclear or cytoplasmic lncRNAs ( Chen, 2016 ). LncRNAs localized in the nucleus typically regulate gene expression in cis, including transcriptional interference or chromatin remodeling ( Jain et al, 2016 ; Zhu et al, 2021 ). On the contrary, LncRNAs localized in the cytoplasm execute regulatory functions via implicating in influencing RNA processing or transport, thereby regulating mRNA degradation or directly altering protein function ( Lin et al, 2016 ).…”
Section: Classification Of Lncrnamentioning
confidence: 99%